2018
DOI: 10.1002/lary.27160
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors in 995 stapes surgeries for primary otosclerosis

Abstract: 4. Laryngoscope, 128:2403-2407, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
4
13
0
8
Order By: Relevance
“…First, the logistic regression analysis showed that a smaller ABG at 250 Hz, 500 Hz, and 4 kHz was associated with better postoperative results, which is concordant with the results published by Kishimoto et al [2015], who found preoperative ABG at the same frequencies to be prognostic factors for better postoperative outcomes. A smaller ABG as a positive prognostic factor shown in this study is congruent with other studies [Ueda et al, 1999;Kishimoto et al, 2015;Khorsandi et al, 2018]. Indeed, Khorsandi et al [2018] recently reviewed 995 stapes surgeries and found that a smaller preoperative ABG was associated with a higher chance of better postoperative ABG closure (OR = 0.90; p < 0.001).…”
Section: Factors Associated With Better Outcomessupporting
confidence: 92%
See 3 more Smart Citations
“…First, the logistic regression analysis showed that a smaller ABG at 250 Hz, 500 Hz, and 4 kHz was associated with better postoperative results, which is concordant with the results published by Kishimoto et al [2015], who found preoperative ABG at the same frequencies to be prognostic factors for better postoperative outcomes. A smaller ABG as a positive prognostic factor shown in this study is congruent with other studies [Ueda et al, 1999;Kishimoto et al, 2015;Khorsandi et al, 2018]. Indeed, Khorsandi et al [2018] recently reviewed 995 stapes surgeries and found that a smaller preoperative ABG was associated with a higher chance of better postoperative ABG closure (OR = 0.90; p < 0.001).…”
Section: Factors Associated With Better Outcomessupporting
confidence: 92%
“…A smaller ABG as a positive prognostic factor shown in this study is congruent with other studies [Ueda et al, 1999;Kishimoto et al, 2015;Khorsandi et al, 2018]. Indeed, Khorsandi et al [2018] recently reviewed 995 stapes surgeries and found that a smaller preoperative ABG was associated with a higher chance of better postoperative ABG closure (OR = 0.90; p < 0.001). We agree with the authors of this study who hypothesized that patients with larger ABG may have multiple otosclerosis lesions, or a more severe otosclerotic process.…”
Section: Factors Associated With Better Outcomessupporting
confidence: 92%
See 2 more Smart Citations
“…In another study that was published by Mohammad Khorsandi et al in 2018, the medical records of 995 patients with otosclerosis undergoing stapedectomy or stapedotomy was retrospectively investigated. The success rate of surgery in this study was reported 93.4% and it was said that the diameter of the prosthesis had no effect on the success rate, but the female gender and right ear involvement are reported as a prognostic factor in the good surgical outcome [14]. In this study, the size and diameter of the prosthesis were not related to auditory outcome and postoperative complications.…”
Section: Discussionmentioning
confidence: 51%